Imperial America : Reflections on the United States of Amnesia - Vidal, Gore, 1925-2012 (New York Nation Books, 2005)
Presents a series of articles and essays criticizing recent developments in American government and foreign policy, especially during the administration of George W. Bush.
Include Index
Keywords: United States -- Politics and government -- National security